2008
DOI: 10.1089/tea.2007.0122
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Cultivation of Integrin α6β1–Expressing Salivary Gland Graft Cells: A Model for Use with an Artificial Salivary Gland

Abstract: Regeneration of the salivary glands' (SGs) normal function for patients with cancer of the head and neck treated with irradiation would be a major contribution to their quality of life. This could be accomplished by re-implantation of autologous SG cells into the residual irradiated tissue or by implantation of tissue-engineered artificial SGs. Both methods depend on the isolation of cells able to propagate and differentiate into SG epithelial cells. Recently, it has been shown that SG integrin alpha(6)beta(1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The relationship between the populations of putative progenitor cells so far identified in the salivary glands [15, 24, 25] is not yet clear. Ascl3+ progenitor cells are located in the ducts in vivo , as are the basal cell Krt5+ progenitors [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the populations of putative progenitor cells so far identified in the salivary glands [15, 24, 25] is not yet clear. Ascl3+ progenitor cells are located in the ducts in vivo , as are the basal cell Krt5+ progenitors [4].…”
Section: Resultsmentioning
confidence: 99%
“…A number of progenitor cell populations have been identified in the salivary gland [1, 2, 4, 5, 24, 25]. In addition to Ascl3, c-Kit and Keratin 5 also mark progenitor cells [4, 5].…”
Section: Discussionmentioning
confidence: 99%
“…showed that the CD24 + CD117 + Sca1 + subpopulation derived from mouse salispheres augments acinar function and restores saliva secretion17. Conversely, murine SG stem/progenitor cells isolated by adherent cell culture have been shown to express MSC markers (CD29, CD44, CD49f, and CD90), as well as c-Kit and Sca-1718192021.…”
Section: Discussionmentioning
confidence: 99%
“…Further study of the Kit-expressing cells also showed that this cell population is located in the ducts of the adult SMG [44]. In addition, stem/progenitor cells of the ducts that were activated in response to injury were shown to express markers Sca1 and Kit [45,46], α6β1-integrin [47] or CD49f (α6-integrin) and Thy1 [48,49]. Furthermore, Ascl3, a transcription factor, also marks a stem/progenitor population that is localized in the salivary ducts [50].…”
Section: Salivary Gland Biogenesismentioning
confidence: 99%